EFEKTIVITAS PROGRAM PEMBIAYAAN MIKROFINANCE DESA OLEH BAZNAS DALAM MENDORONG PENGEMBANGAN USAHA MIKRO MUSTAHIK - Jasri Jasri; Andi Syarifah Wahdah; Muhammad Ridwan; Abdul Malik (LP2M Universitas Bina Bangsa, 2023)
This study is intended to identify how the implementation of the village microfinance program by Baznas affects the development of micro-enterprises owned by mustahik in BAZNAS, Maros Regency. The research method used in this study is descriptive qualitative research. Data collection methods include observation, face-to-face interviews, and documentation. Research findings show that the implementation of the Village Microfinance program by the National Amil Zakat Agency in Maros Regency contributes significantly to micro-entrepreneurs in developing their businesses, especially for those who have difficulty accessing capital. This program also helps micro-entrepreneurs to overcome the impact of declining income due to the impact of the COVID-19 pandemic. In addition to financial support, mustahik engaged in the micro business sector also receive market access assistance from the Village Microfinance program by BAZNAS, making it easier for them to promote the business products they produce